A model linking digital media dependence, exercise empowerment, and social physique anxiety among emerging adulthood college students - Luo, Lin; Yuan, Junfeng; Bi, Siyuan; Wang, Yanlin (Frontiers in Psychology, 2023)
Background/Objective: Social physique anxiety (SPA) is a prevalent psychological issue among emerging adults, regardless of gender. Many studies have shown that high levels of SPA are associated with various negative consequences on both physical and mental well-being.Considering the potential severity of SPA's consequences and its high prevalence among emerging adults, it is imperative to investigate the factors and mechanisms that contribute to SPA in this population. Although prior studies have identified associations between emerging adulthood, digital media use, and SPA in young individuals, the underlying mechanisms remain unclear. The objective of this study is to examine the associations between SPA, emerging adulthood characteristics, digital media dependency, and exercise empowerment . Methods: In this cross-sectional study, Chinese college students were recruited using snowball sampling. The study utilized an online survey to assess SPA, emerging adulthood characteristics, digital media dependency, and exercise empowerment. The collected data was analyzed using path analysis. Results: A total of 1661 Chinese college students (mean age=19.63±0.32 years, 44.97% male) were included in this study. The results showed that SPA exhibited positive correlations with responsibility and instability in emerging adulthood characteristics, digital media dependency, and exercise empowerment. Additionally, digital media dependency showed positive correlations with responsibility and instability, as well as with exercise empowerment. Furthermore, exercise empowerment demonstrated positive correlations with self-exploration, responsibility, instability, and possibilities in emerging adulthood characteristics. SPA can be directly influenced by digital media dependency, self-exploration, and instability.Furthermore, digital media dependency has a positive indirect impact on SPA through exercise empowerment. Similarly, self-exploration also has a positive indirect impact on SPA through exercise empowerment. On the other hand, instability has a negative indirect impact on SPA through exercise empowerment. Conclusion: This study provides new insights into the complex correlations with emerging adulthood characteristics, digital media dependency, exercise empowerment, and SPA. Instability, self-exploration in emerging adulthood characteristics ,as well as digital media dependency, have the potential to influence SPA among college students through exercise empowerment Interventions and strategies aimed at addressing these psychological factors may prove beneficial in reducing SPA among emerging adults, especially college students.